2015
DOI: 10.1093/neuonc/nov172
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression and prognostic impact in glioblastoma

Abstract: The incidence of PD-L1 expression in GBM patients is frequent but is confined to a minority subpopulation, similar to other malignancies that have been profiled for PD-L1 expression. Higher expression of PD-L1 is correlated with worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
383
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(418 citation statements)
references
References 44 publications
(29 reference statements)
25
383
4
6
Order By: Relevance
“…A recent smaller study of 94 GB tumors showed PD-L1 positive staining in greater than 60 % of tumors, but most with a small percentage of cell surface expression. Expression of PD1 and PD-L1 in this study was found to be a negative prognostic factor for survival [28].…”
Section: Clinical Datasupporting
confidence: 53%
“…A recent smaller study of 94 GB tumors showed PD-L1 positive staining in greater than 60 % of tumors, but most with a small percentage of cell surface expression. Expression of PD1 and PD-L1 in this study was found to be a negative prognostic factor for survival [28].…”
Section: Clinical Datasupporting
confidence: 53%
“…A recent study showed robust and diffuse expression of PD-L1 assessed by immunohistochemistry in newlydiagnosed as well as recurrent GBM (88% vs. 72.2%, respectively), which is a relatively high percentage compared to other cancer types such as melanoma (134). Higher expression of PD-L1 in tumor tissue correlated with worse outcome in another study with 94 patients with GBM (135). Because of the promising pre-clinical experiments, proven activity in the CNS and the presence of targets in GBM tumor tissue, clinical trials with specific immune checkpoint inhibitors are warranted in patients with GBM in newly diagnosed as well as recurrent settings.…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 94%
“…Drugs targeting PD-1 or PD-L1 are now also being investigated in the context of primary brain tumors, mainly glioblastoma, in which these molecules are frequently expressed [44,45]. A phase III trial comparing the PD-1 antibody nivolumab with bevacizumab in patients with recurrent glioblastoma has completed accrual (NCT02017717).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%